KUALITAS PELAYANAN PUBLIK DI KANTOR UTD PMI KOTA PEKANBARU - SUDARYANTO SUDARYANTO (Universitas Pahlawan Tuanku Tambusai, 2020)
Blood donor activities are specifically the responsibility of the Indonesian Red Cross Blood Transfusion Unit Pekanbaru City. In addition, there is also the authority of the hospital to form a Blood Bank and for certain cases special handling becomes the authority of the central government. Given the importance of blood for humanitarian missions, it is necessary to have the active involvement of all elements of society to donate blood regularly. From the observations made, it was found that problems were still found by people who were confused in administrative matters. Then there are still many Pekanbaru City residents who have never done blood donor activities, not all agencies that require employees to do blood donations. Therefore it is necessary to do qualitative research to overcome these problems using the Lijan Sipoltak theory. The informants used were blood donor and community apparatus units. As a result, the quality of public services has run according to applicable regulations but still needs improvement.